2009
DOI: 10.1186/1742-4682-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Using a human cardiovascular-respiratory model to characterize cardiac tamponade and pulsus paradoxus

Abstract: Background: Cardiac tamponade is a condition whereby fluid accumulation in the pericardial sac surrounding the heart causes elevation and equilibration of pericardial and cardiac chamber pressures, reduced cardiac output, changes in hemodynamics, partial chamber collapse, pulsus paradoxus, and arterio-venous acid-base disparity. Our large-scale model of the human cardiovascular-respiratory system (H-CRS) is employed to study mechanisms underlying cardiac tamponade and pulsus paradoxus. The model integrates hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…There are also many other studies using various models to simulate pulsus paradoxus and try to disclose its mechanism [22][26]. In common with our study, most of these studies have noticed the important role of septal swing in the occurance of pulsus paradoxus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are also many other studies using various models to simulate pulsus paradoxus and try to disclose its mechanism [22][26]. In common with our study, most of these studies have noticed the important role of septal swing in the occurance of pulsus paradoxus.…”
Section: Discussionsupporting
confidence: 82%
“…In common with our study, most of these studies have noticed the important role of septal swing in the occurance of pulsus paradoxus. Ramachandran et al [22] used their complex H-CRS model to simulate hemodynamic and respiratory changes associated with tamponade clinically, focusing particularly on the role of the interventricular septum. Their study showed that pulsus paradoxus was a multifactorial phenomenon which is related with septal motion, atrioventricular and right-left ventricular interactions, pulmonary blood pooling, and the depth of respiration.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many other studies using various models to simulate pulsus paradoxus and try to disclose its mechanism [22][23][24][25][26]. In common with our study, most of these studies have noticed the important role of septal swing in the occurance of pulsus paradoxus.…”
Section: Previous Studies and Theories About The Mechanism Of Pulsus supporting
confidence: 59%
“…Both parallel and series biventricular interdependence mechanisms should contribute to decrease left ventricle filling and hence to decrease LVSV at inspiration if the left ventricle is preload-dependent. RAMACHANDRAN et al [36] used a human cardiovascular-respiratory system model that simulates haemodynamic and respiratory changes associated with tamponade clinically. They showed that both the parallel and series interactions have an equal and significant contribution to LVSV respiratory variation, and hence to pulsus paradoxus.…”
Section: Pulsus Paradoxus In Cardiac Tamponadementioning
confidence: 99%